Emergence of Besnoitia besnoiti in Belgium - Laurent Delooz; Julien Evrard; Serge Eugene Mpouam; Claude Saegerman (Pathogens, 2021)
Bovine besnoitiosis is a cattle disease caused by a protozoan parasite called Besnoitia besnoiti. It is of serious economic concern to the cattle industry and also compromises animal welfare. For several years, it has been considered an emerging disease in some countries and regions located in the north of Europe far away from the known endemic areas in the south. This study describes the situation in the southern part of Belgium, where the parasite was recently introduced through imports of animals coming from departments of France where the disease was present. It details the detection of clinical cases as well as disease transmission features related to contacts during grazing and sales of infected cattle. A tracking and monitoring system was quickly set up and detected twelve outbreaks. Several cattle were controlled, but the lack of appropriate regulations weakens disease-management efforts. Hopefully, this predictable and silent introduction triggers the awareness of decision-makers about the need for an appropriate prevention and control policy, law enforcement, and the implementation of necessary measures to avoid bovine besnoitiosis becoming endemic in Belgium or other non-endemic countries. In addition, more proactive surveillance is required from authorities through threat analysis in the context of the risk of emergence or re-emergence of infectious animal diseases.